Private pensions and the public interest : a symposium - American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1970)
This volume contains the proceedings of a symposium held in Washington, D.C., in May 1969 by the American Enterprise Institute for Public Policy Research. The symposium was designed to explore the areas of discussion and controversy created by the debate on the proper role of the nation's private pension systems. Emphasis was directed to current views on the respective roles of the public and private pension systems, the current tax, vesting, and funding status of private plans, and the public policy issues involved in legislative proposals for broader government regulation of the private pension plan structure.
"Sponsored by American Enterprise Institute for Public Policy Research."
Includes bibliographical references.
rpm 28/03/2018
Loans
Keywords: Old age pensions; Retirement income; Public interest